Pemaknaan Fungsi dan Bentuk pada Interior Restoran Dae Jang Geum Yogyakarta - Graceshella Wijaya; mariana wibowo; dody wondo (Intra, 2013)
Restaurant bussiness is one of the most developed and popular today, especially in big cities. Therefore, businesses are competing to attract the attention of the public, not only of the dishes served, but also the atmosphere and the interior of the restaurant is unique and interesting. One of the restaurant’s interior that attracts attention is the Dae Jang Geum restaurant Yogyakarta, because the restaurant is adapting very interesting culture, the culture of Korea, in particular the form of the Kingdom of Korea, namely during the Joseon Dynasty, established in July 17, 1392 and it is this that makes restaurant this looks interesting and different from other restaurants. The subject of this research focused on aspects of the meaning, function, and form the interior of the restaurant by using “descriptive qualitative” research method that performs a number of ways, namely interviews, field surveys, and literature. The results showed that the interior application of Dae Jang Geum restaurant get Korean cultural influence can be seen in the interior design and their functions and forms of decorative elements that contain a lot of meaning and mixed with Javanese culture, a little bit precisely in the main area of this restaurant, because it is influenced by aspects this neighborhood restaurant is located in the area of Java.